Trait responses of invasive aquatic macrophyte congeners: colonizing diploid outperforms polyploid - Grewell, Brenda J. (AoB Plants, 2016)
Understanding traits underlying colonization and niche breadth of invasive plants is key to developing sustainable management solutions to curtail invasions at the establishment phase, when efforts are often most effective. The aim of this study was to evaluate how two invasive congeners differing in ploidy respond to high and lowresource availability following establishment from asexual fragments. Because polyploids are expected to have wider niche breadths than diploid ancestors, we predicted that a decaploid species would have superior ability to maximize resource uptake and use, and outperform a diploid congener when colonizing environments with contrasting light and nutrient availability. A mesocosm experiment was designed to test the main and interactive effects of ploidy (diploid and decaploid) and soil nutrient availability (low and high) nested within light environments (shade and sun) of two invasive aquatic plant congeners. Counter to our predictions, the diploid congener outperformed the decaploid in the early stage of growth. Although growth was similar and low in the cytotypes at low nutrient availability, the diploid species had much higher growth rate and biomass accumulation than the polyploid with nutrient enrichment, irrespective of light environment. Our results also revealed extreme differences in time to anthesis between the cytotypes. The rapid growth and earlier flowering of the diploid congener relative to the decaploid congener represent alternate strategies for establishment and success.